Recommendations for home blood pressure monitoring in Latin American countries: A Latin American Society of Hypertension position paper. Issue 4 (12th February 2020) - Villar, Raúl; Sánchez, Ramiro A.; Boggia, José; Peñaherrera, Ernesto; Lopez, Jesús; Barroso, Weimar Sebba; Barbosa, Eduardo; Cobos, Leonardo; Hernández Hernández, Rafael; Octavio, José Andrés; Parra Carrillo, José Z.; Ramírez, Agustín J.; et al.
Abstract: Out‐of‐office blood pressure (BP) monitoring appears to be a very useful approach to hypertension management insofar it allows to obtain multiple measurements in the usual environment of each individual, allows the detection of hypertension phenotypes, such as white‐coat and masked hypertension, and appears to have superior prognostic value than the conventional office BP measurements. Out‐of‐office BP can be obtained through either home or ambulatory monitoring, which provide complementary and not identical information. Home BP monitoring yields BP values self‐measured in subjects' usual living environment; it is an essential method for the evaluation of almost all untreated and treated subjects with suspected or diagnosed hypertension, best if combined with telemonitoring facilities, also allowing long‐term monitoring. There is also increasing evidence that home BP monitoring improves long‐term hypertension control rates by improving patients' adherence to prescribed treatment. In Latin American Countries, it is widely available, being relatively inexpensive, and well accepted by patients. Current US, Canadian, Japanese, and European guidelines recommend out‐of‐office BP monitoring to confirm and refine the diagnosis of hypertension.